Optimization of methylene blue adsorption via functionalized activated carbon using response surface methodology with central composite design - Saafie, N. (Trans Tech Publications Ltd, 2020)
The commercial activated carbon (AC) with enhanced adsorption performance capacity was studied via green functionalization. The adsorption of methylene blue (MB) from aqueous solution by deionized-water functionalized activated carbon (DFAC) was investigated in a laboratory-scale batch mode. The interaction effects of different operating parameters; adsorbent dosage (1-5 g/L), pH (2-12) and agitation speed (100-200 rpm) were studied. The ANOVA results suggested the quadratic model and the analyzed model were well fitted. The higher correlation coefficient, R2 value of 0.93 and low p-value (0.0002) indicating the fitness of the response surface quadratic model developed. The optimum conditions were found to be the adsorbent dosage of 4.7 g/L, pH of 12 and agitation speed of 150 rpm, in which 99.74 of MB removal was achieved. Additionally, the confirmatory experiment was conducted to evaluate the accuracy of the optimized conditions in which the range of deviation is was 4.07. Â© 2020 Trans Tech Publications Ltd, Switzerland.